Infrastructure of citizenship and subjecthood. Traditional authorities vs National Government: a case study of Tlokweng village, North West, South Africa - Dlamini, Tlhalefo (My University, 2019)
The former “homeland” areas of South Africa continue to be spaces in which underdevelopment is still severe. The post-apartheid South African state has recognized that citizenship requires more than simply legal rights being restored but also substantive interventions to actively improve the quality of life of individuals. This has taken the form of housing and basic service delivery as instruments towards poverty eradication. The primary delivery vehicle for these is through infrastructural interventions by the local government, through the Independent Development Plans (IDP’s) and its guidelines the municipal system Act, no.32 of 2000. In many rural parts of the country, and especially the former homeland areas, service delivery remains critically slow and responsibility for delivery is often confused between local municipalities and traditional authorities by traditional subjects. Whereas, the goals of post-apartheid legislation may be substantive citizenship. The reality is that many rural people live as what Mamdani (1996) would refer to as subjects with very little realistic access even to the minimum legal rights of citizenship. Nevertheless, identification and belonging to a traditional authority remains very strong among many communities in rural South Africa (Mamdani,1996). This research project investigates the social and political subjectivities in Tlokweng, a rural village in the North West Province, at the intersection between traditional authority and local government. It uses the materiality of infrastructure as a lens through which to explore the ways in which these subjectivities are both claimed and resisted, and contributes to a literature on the intersection of infrastructures and citizenship in the global South.
This dissertation is submitted to the Facility of Science, to the University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Science.